SOCIAL TRANSFORMATION AS A SYSTEMIC PROCESS: A PHILOSOPHICAL AND INTERDISCIPLINARY ANALYSIS (Scientific journal of the Fergana State University, 2026)
This article examines social transformation as a multi-level and systemic process that affects the economy, culture, politics, and value orientations of society. The author draws upon the philosophical views of K. Marx, É. Durkheim, M. Weber, as well as contemporary theorists of modernization and globalization.